The Fifth Edition of the UBS Greek New Testament. Issue 2 (August 2014) - Voss, Florian
The fifth edition of The Greek New Testament is intended to enable its readers to read, understand, and translate the New Testament in its original language in as competent and skilled a manner as possible. To meet this aim the edition was revised in two ways. First, several improvements have been introduced that concern the entire New Testament. Second, in the Catholic Epistles, the edition has been made consistent with the Editio Critica Maior of the Greek New Testament, including textual changes in the base text.